Progressive Myoclonic Epilepsy: Review Article with A Case Report of Lafora Disease (Bangladesh Journal of Child Health, 2018)
Progressive myoclonic epilepsy (PME) is an autosomal recessive, apparently a rare complex epilepsy syndrome. Among different types of PME, lafora body disease is more quickly progressive usually fatal within 2nd and 3rd decade. They are characterized by childhood or adolescent onset difficult to control multiple type seizures including myoclonous, generalized tonic clonic, absences, psychomotor regression with ataxia, dementia, dysarthria, visual hallucinations, and other general features. Early suspicion is important that leads to the rational diagnostic workout. The electro-clinical criteria would help a lot to exclude the benign epilepsy syndrome such as juvenile myoclonic epilepsy (JME) and suspect PME at the early stage of the complex epilepsy syndrome. Diagnosis is further clarified and confirmed by finding lafora body in skin and genetic study. Genetic mutation found in more than 87% cases in EPM2A gene or the EPM2B also known as NHLRC1 gene and are inherited in an autosomal recessive manner. EMP2A gene is located on chromosome 6q24. They are reported from Mediterranean basin, central Asia, India, Pakistan, northern Africa and Middle East where consanguineous marriage is common. We report a diagnosed case for the first time in Bangladesh. With the detail clinical history, rational use of the available investigation tools and clinical suspicion, diagnosis of the disorder at its early stage is possible. The rapid progress in genetic therapy would be a great hope in near future.Bangladesh J Child Health 2018; VOL 42 (3) :138-147